Characterization of Chirp Properties of an 850 nm Single-Mode Multi-Aperture Vertical-Cavity Surface-Emitting Laser and Analysis of Transmission Performance over Multimode and Single-Mode Fibers - Xin Chen; Nikolay Ledentsov; Abdullah S. Karar; Jason E. Hurley; Oleg Yu. Makarov; Hao Dong; Ahmad Atieh; Ming-Jun Li; Nikolay Ledentsov (Photonics)
By measuring the transfer function of the single-mode multi-aperture vertical-cavity surface-emitting laser (SM MA VCSEL) transmitting over a long single-mode fiber at 850 nm, we confirm that the chirp of the SM MA VCSEL under study is dominated by transient chirp with an alpha value of −3.81 enabling a 19 GHz bandwidth over 10 km of single-mode fiber. The detailed measurement of the VCSEL with different bias currents also allows us to recover other key characteristics of the VCSEL, thereby enabling us to practically construct the optical eye diagrams that closely match the experimentally measured ones. The link-level transfer function can be obtained using an analytical equation including effects of modal dispersion and laser chirp–chromatic dispersion (CD) interaction for an MMF of a given length and bandwidth grade. The narrow linewidth and chirp characteristics of the SM MA VCSEL enable transmission performance that surpasses that of conventional MM VCSELs, achieving comparable transmission distances at moderate modal bandwidths for OM3 and OM4 fibers and significantly longer reaches when the modal bandwidth is higher. The transmission performance was also confirmed with the modeled eye diagrams using extracted VCSEL parameters. The chirp properties also provide sufficient bandwidth for SM MA VCSEL transmission over kilometer-scale lengths of single-mode fibers at a high data rate of 100G or above with sufficient optical power coupled into the fibers. Advanced transmission distances are possible over multimode and single-mode fibers versus chirp-free devices.